Pouvoir antioxydant et teneurs en composés phénoliques de deux espèces du genre Albertisia: Albertisia cordifolia (Mangenot & J. Miège) Forman et Albertisia scandens (Mangenot & J. Miège) Forman (Menispermaceae) - Awa, Diomande; Konan, Yao; Youssouf, Sylla; Honora, Tra Bi Fézan; Adama, Bakayoko; Witabouna, Kone Mamidou (European Scientific Journal, ESJ, 2018)
Albertisia cordifolia and Albertisia scandens are medicinal plants of Menispermaceae family, used in traditional medicine in Côte d’Ivoire. Both species were evaluated in vitro for antioxidant activity and contents of total polyphenols, flavonoids and condensed tannins. In the present study, six extracts (aqueous, ethyl acetate and ethanolic) were prepared from the leaves of A. cordifolia and the whole plant of A. scandens. The antioxidant assays were performed using the DPPH free radical scavenging and FRAP tests. Total polyphenols, flavonoids and condensed tannins were determined by spectrophotocolorimetric method. The results revealed that the yields of extraction are between 4.69-12.27%. The percentages of DPPH inhibition European Scientific Journal October 2018 edition Vol.14, No.30 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 129 were between 33.84 and 69.21% while ascorbic acid and trolox gave 93.66% and 59.77% respectively. The IC50 values ranged from 20 to 280 μg ml-1 for DPPH. The ethyl acetate extract of A. cordifolia was the most active (IC50 = 20 μg ml-1 ) compared to the other extracts and trolox (28 μg ml-1 ). The antioxidant capacities (DPPH) varied between 1.90 and 7.18 mg ET g -1MS. For FRAP, the extracts showed a dose-dependent activity with antioxidant capacities between 0.80 and 2.71 mg ET g -1MS. The best iron reducing powers were obtained for the aqueous extract of A. scandens (2.71 ± 0.59 mg ET g -1MS) and ethanolic extract of A. cordifolia. These results show that these two species may play a role in the prevention of oxidative stress related diseases.